Effects of different dietary energy levels on growth performance, meat quality and nutritional composition, rumen fermentation parameters, and rumen microbiota of fattening Angus steers - Chen, Kaihao; Shui, Yanghaoer; Deng, Ming; Guo, Yongqing; Sun, Baoli; Liu, Guangbin; Liu, Dewu; Li, Yaokun (Frontiers in Microbiology, 2024)
In this study, 27 Black Angus steers, averaging 22 (±1) months in age and 520 ± 40 kilograms in wei ght, were randomly divided into three groups, with nine individuals in each group. Diets of varying e nergy levels were administered: the low-energy (LE) group at 6.657 MJ/kg, the medium-energy (ME) group at 7.323 MJ/kg, and the high-energy (HE) group at 7.990 MJ/kg. A pre-feeding period of 14 d ays was followed by a 90-day main experimental phase. Results indicated that, after 90 days of feedi ng, both the HE and ME groups exhibited significantly higher average daily weight gain (ADG) com pared to the LE group (P < 0.05). The feed-to-weight ratios in both the HE and ME groups were lowe r than that in the LE group (P < 0.05). Furthermore, the HE group demonstrated a significantly higher crude fat content in the longissimus dorsi muscle compared to the LE group (P < 0.05), with the total fatty acid content in the muscle also surpassing that in the ME and LE groups (P < 0.05). With the in crease in dietary energy levels, the diversity of the rumen microbial community decreased (P < 0.05), and significant differences in bacterial community structure were observed between the LE and HE g roups (P < 0.05). In the phylogenetic trees, the LE, ME, and HE groups demonstrate different evoluti onary trajectories. Utilizing Pearson correlation analysis, This study conducted an association analysi s between the rate of rumen fermentation parameters (FPR) and rumen microbiota, uncovering the rel ationships of eight phyla and nine genera with rumen fermentation parameters. This study explores th e impacts of high-energy level diets on Angus steers from various perspectives. The objective was to identify the optimal dietary energy level for finishing Angus cattle, aimed at enhancing beef quality, i ncreasing economic returns, and supporting data-driven development of standardized production proc edures for Angus cattle.